Globalization and the 'New Enterprise' - Dalia Marin; Thierry Verdier (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2002)
Globalization has been identified by many experts as a new way firms organize their activities and as the emergence of human capital as the new stakeholder of the firm. This paper surveys recent work which examines the role of trade integration for these changes in corporate organization. More intense competition and the change in the pattern of specialization following trade liberalization make it both more likely that an organizational equilibrium emerges in which power is delegated to lower levels of the firms' hierarchy empowering human capital. Furthermore, trade integration leads to waves of outsourcing and to a convergence in corporate cultures across countries.
urn:nbn:de:bvb:19-epub-11-9
Keywords: F12; D23; L1; L2; 330; international trade with imperfect competition; corporate governance; theory of the firm; empowerment; outsourcing